From farm to fork: determinants of supplier-retailer relation in organic agri-food supply chain on EU Eastern – Western approach - Kardos, Mihaela; Popa, Ion; Bacoș, Ioan Bogdan; Gabor, Manuela Rozalia (Journal of Business Economics and Management, 2025)
The European Union’s Farm to Fork Strategy, embedded within the Green Deal, aims to create equitable and sustainable food systems, fostering environmentally responsible practices and addressing challenges comprehensively throughout the agri-food supply chain. Organic farming plays an important role in this transition, particularly in the context of the circular economy. This study explores the key determinants influencing supplier-retailer relationships in the organic agri-food supply chain, focusing on the interaction between Romanian suppliers and retailers from Germany, Austria, and Switzerland. Using a mixed-methods approach that combines quantitative and qualitative analysis, the research identifies price, quality, and trust as essential factors shaping demand. Given Romania’s growing organic agriculture sector and the increasing consumption of organic products in German-speaking markets, this study highlights both challenges and opportunities for enhancing trade relations. As one of the first investigations into the East-West dynamics of the EU organic agri-food supply chain, the findings provide valuable insights for strengthening sustainable agriculture and market integration in Romania. It is also relevant for other Eastern European countries emphasizing the importance of a strong green agri-food sector throughout the European Union, as well as coordinated efforts along the supply chain.